Dynamic QAM Mapping for Physical-Layer Security Using Digital Chaos - Amber Sultan; Xuelin Yang; Adnan A. E. Hajomer; Syed B. Hussain; Weisheng Hu (IEEE Access, 2018)
This paper proposes and experimentally demonstrates a physical-layer data encryption scheme using multi-fold chaotic mapping of quadrature amplitude modulation (QAM) symbols in orthogonal frequency-division-multiplexed passive optical network (OFDM-PON). Dynamic radius and phase offsets are added in the standard QAM during QAM mapping on constellation using digital chaos. Due to the dynamic chaotic radius and phase offsets, the QAM symbols are mapped over the entire constellation plane, and thus the random, flexible QAM mapping is reconstructed to provide high-level security during data transmission. Since the chaotic offsets along with the data permutations are independently predetermined by a hyper digital chaos, the multi-fold data encryption creates an overall key space of ~10340 to enhance the physical-layer security. Successful transmission experiment of 9.4-Gb/s, 16-QAM encrypted OFDM data is demonstrated over a 22-km standard single-mode fiber in OFDM-PON. Moreover, with the use of dynamic mapping of QAM symbols, the transmission performance is not significantly degraded after implementing the proposed multi-fold secure data encryption.